2014
DOI: 10.1107/s160057751401056x
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of an X-ray beam modified by a photonic crystal

Abstract: A method of calculating the transmission of hard X-ray radiation through a perfect and well oriented photonic crystal and the propagation of the X-ray beam modified by a photonic crystal in free space is developed. The method is based on the approximate solution of the paraxial equation at short distances, from which the recurrent formula for X-ray propagation at longer distances is derived. A computer program for numerical simulation of images of photonic crystals at distances just beyond the crystal up to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Theory of Ptychographic Experiment : Propagation of X‐rays through the colloidal crystal can be described by the paraxial wave equation, which in Cartesian coordinates can be presented as2ikE(r)z=normalΔE(r)+k2χ(r)E(r)where E(r) is the complex‐valued wave amplitude, k = 2π/λ is the wavenumber, λ is the wavelength of X‐rays, Δ ⊥ is the transverse part of the Laplace operator and χ(r) is the complex‐valued susceptibility of the sample. Here the following coordinate system was adopted with the z ‐axis along the optical axis of a narrowly collimated coherent X‐ray beam and r = { x , y } is a 2D vector in transverse direction along the surface of the colloidal crystal film, as shown in Figure .…”
Section: Theory and Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theory of Ptychographic Experiment : Propagation of X‐rays through the colloidal crystal can be described by the paraxial wave equation, which in Cartesian coordinates can be presented as2ikE(r)z=normalΔE(r)+k2χ(r)E(r)where E(r) is the complex‐valued wave amplitude, k = 2π/λ is the wavenumber, λ is the wavelength of X‐rays, Δ ⊥ is the transverse part of the Laplace operator and χ(r) is the complex‐valued susceptibility of the sample. Here the following coordinate system was adopted with the z ‐axis along the optical axis of a narrowly collimated coherent X‐ray beam and r = { x , y } is a 2D vector in transverse direction along the surface of the colloidal crystal film, as shown in Figure .…”
Section: Theory and Experimental Sectionmentioning
confidence: 99%
“…In a thick colloidal film, the ESW may be determined by a multislice approach . In a thin colloidal film, the free‐space propagation, which is represented by the propagation operator Δ ⊥ in Equation , can be neglected, and the differential equation gives relatively simple solution for the object functionO(x,y)=exp[]ik2true0normaldfalse(x,yfalse)χfalse(x,y,zfalse)normaldzThe complex‐valued susceptibility can be represented as a sum of real and imaginary partsχ(x,y,z)=χ (x,y,z)+iχ(x,y,z)and after substitution of Equation in Equation , the complex valued object function can be written asO(x,y)=||Ofalse(x,yfalse)normaleiϕ(x,y)=exp[]k2true0normaldfalse(x,yfalse)χfalse(x,y,zfalse)normaldzexp[]ik2true0normaldfalse(x,yfalse)χfalse(x,y,zfalse)normaldzHere the amplitude of the object function is defined as|O(x,y)| = exp []k2true0normaldfalse(x,y…”
Section: Theory and Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why the accuracy of the approximation (1) must be analyzed. Kohn et al (2018) carried out a detailed analysis of the results of two methods: phase-contrast imaging and a more accurate iterative method developed for studying photonic crystals (Kohn & Tsvigun, 2014;Kohn, Snigireva & Snigirev, 2014). It has been shown that the phase-contrast method based on the transmission function (1) is fairly accurate when applied to specimens containing the number of tubules N 100 along the beam.…”
Section: Computer Simulations Of Phase-contrast Images Of a Model Objmentioning
confidence: 99%
“…The field of applications of refractive optics is not limited to beam conditioning, but can be extended into the area of Fourier optics, as well as coherent diffraction and imaging techniques [12][13][14][15]. Using the intrinsic property of the refractive lens as a Fourier transformer, the coherent diffraction microscopy and high-resolution diffraction methods have been proposed to study 3-D structures of photonic crystals and mesoscopic materials [16][17][18].…”
Section: Future Gamma Systems Roundmentioning
confidence: 99%